Transcriptomic response of minor millets to abiotic stresses - Sanku, Gowthami; Rajasekaran, Ravikesavan; Boopathi, Narayanan Manikanda; Krishnamoorthy, Iyanar; Santhanakrishnan, Vichangal Pridiuldi; Mani, Vetriventhan (Frontiers in Sustainable Food Systems, 2024)
Global food and nutritional security are being threatened by abiotic stresses such as drought, salinity, cold, and heat, owing to the rapid and deleterious effects of climate change. Millets represent an incredibly promising agricultural crop in terms of their potential to ensure global food security by virtue of their resiliency against climate change and escalating demand for nutritious food and feed. Considering their durability against climate change and the increasing demand for nutritional food and feed, millets, which refers to the diverse class of small-seeded C4 panicoid grasses, endure remarkable potential for safeguarding the world’s food supply. With a rapid surge in the availability of genomic information through microarray and next-generation sequencing, transcriptomics facilitated the extensive examination and quantification of shifts brought about by abiotic stresses. This stipulates an imperative way of ascertaining the expression of vital genes. This technological advancement targeted toward deciphering the gene expression patterns underpinning the molecular mechanisms/pathways. Other techniques, for instance, genome-wide expression analysis which provides insights into the regulatory networks controlling the cellular processes, genome-wide location analysis which elucidates the control over genes by the transcriptional regulatory proteins, and genomic selection strengthens the reliability of stress tolerance predictions in millet breeding populations. This review emphasizes the impact of transcriptomics on millet improvement by collating the differentially expressed genes (DEGs), and transcription factors (TFs) specific to abiotic stress response in millets which could open advantageous avenues with intriguing opportunities in breeding cultivars for climate resilience.